2009
DOI: 10.1186/1475-925x-8-24
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-structure interaction of a patient-specific abdominal aortic aneurysm treated with an endovascular stent-graft

Abstract: Background: Abdominal aortic aneurysms (AAA) are local dilatations of the infrarenal aorta. If left untreated they may rupture and lead to death. One form of treatment is the minimally invasive insertion of a stent-graft into the aneurysm. Despite this effective treatment aneurysms may occasionally continue to expand and this may eventually result in post-operative rupture of the aneurysm. Fluid-structure interaction (FSI) is a particularly useful tool for investigating aneurysm biomechanics as both the wall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 38 publications
1
57
0
1
Order By: Relevance
“…The insertion of an endograft causes alterations in the hemodynamic environment of the AAA, regarding the pressures and stresses exerted on the AAA sac as well as the flow patterns inside the endograft lumen (Molony et al, 2009). There is a reduction in the intrasac pressure and the stress values on the sac of the stented AAA, leading to sac shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of an endograft causes alterations in the hemodynamic environment of the AAA, regarding the pressures and stresses exerted on the AAA sac as well as the flow patterns inside the endograft lumen (Molony et al, 2009). There is a reduction in the intrasac pressure and the stress values on the sac of the stented AAA, leading to sac shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of a stent-graft has been associated with a decrease in the AAA compliance. 20 Van Herwaarden et al have also reported an increase in AAA wall stiffness after EVAR. 28 This was also confirmed by Long et al, who evaluated the wall movement of the AAA sac after endovascular repair by using tissue Doppler imaging, 29 estimating indices of stiffness, elasticity (pressure strain elastic modulus, Ep) and parameters of sac wall compliance (i.e.…”
Section: Remodeling Of the Aneurysm Wallmentioning
confidence: 94%
“…Molony et al reconstructed computationally preoperative, postoperative and follow-up models of AAA after endovascular exclusion. 20 They calculated the wall stress values and distribution in each model and showed a redistribution of stress patterns along with decrease in their values. The remodeling of the AAA sac can change the sac volume and configuration, which is associated with reduction and redistribution in wall stress patterns.…”
Section: Remodeling Of the Aneurysm Wallmentioning
confidence: 99%
“…Though the hemodynamic model of a rigid tube wall [1][2][3][4] has been widely utilized, it is not able to show the stress-strain properties of solids, which places severe limitations on clinical applications. The model of a flexible tube wall [5][6][7] is not only able to show the deformation of the solid, but also reflects the influence of solid deformation on flow field, which has great potential for application [8]. However, the model fails to show the complex pressure wave of physiology [9] and simulate the propagation of a pulse wave.…”
Section: Introductionmentioning
confidence: 99%